Influences of temperature and salinity on holistic network performability of multi-AUV cooperative systems. (October 2019) - Liang, Qingwei; Ou, Junlin; Xue, Zengxi; Ippolito, Christina
Abstract: This study proposes holistic network performability as a reliability index of multiple autonomous underwater vehicle (AUV) (multi-AUV) cooperative systems and deduces the reliability of communication links. Temperature and salinity vary in different areas of the sea. The influence mechanism of temperature and salinity on holistic network performability is discussed. An example is provided to show the influences of temperature and salinity on holistic network performability. Corresponding trends of holistic network performability with the influences of temperature and salinity can be obtained. The trends show that the holistic network performability of multi-AUV cooperative systems exhibit ladder-like increases with temperature and salinity. In each ladder, the value of holistic network performability changes rapidly at high salinity or low temperature. The study on the change of the reliability of multi-AUV cooperative systems under different temperatures and salinities provides a theoretical basis for the reliability research of multi-AUV cooperative systems and provides reference for future practical application of multi-AUV cooperative systems and other network systems.